(untitled) (Scientific Journal of Research Studies in Future Management, 2025)
Recent technological advancements in artificial intelligence (AI) have reshaped the dimensions of educational leadership. Foresight, as a strategic tool for analyzing trends, scenarios, and potential implications, enables the evaluation of AI’s role in guiding educational institutions. This paper, through a foresight-based approach, explores the threats and opportunities arising from AI integration in educational leadership. Threats such as the replacement of managerial functions by algorithms, reduced human interaction, and ethical concerns pose critical challenges. Conversely, opportunities including personalized learning, big data analytics, evidence-based decision-making, and improved efficiency highlight the transformative potential of AI in education. Drawing on a systematic review of international peer-reviewed studies published in the last five years, along with real-world data, this research proposes a framework for evaluating the future of educational leadership in the AI era. The findings indicate that educational leaders must enhance technological, ethical, and foresight-related competencies to ensure the safe and effective integration of AI. Combining foresight methodologies with educational policy-making will help mitigate risks while maximizing the benefits of technological transformation.